Avaliação do potencial protetor de compostos fenólicos sobre atividades tóxicas induzidas por peçonhas de Bothrops spp. e Crotalus durissus terrificus - Cesar, Pedro Henrique Souza (2016)
Snakebites are considered a serious public health problem that affects 1.2 to 5.5 million people per year, throughout the world. Approximately 125 thousand dies and other 400 thousand survive with permanent sequelae. However serum therapy may prevent systemic damage caused by envenoming, the local effects persists, impairing the quality of life of the victims, as well as its health. Keeping in mind the healing potential of plants secondary metabolites against various comorbidities including snakebites, this work committed to evaluate the phenolic compounds vanillic acid, p-coumaric acid, catechin and epicatechin, against the toxic activities of some Bothrops snakes venoms and Crotalus durissus terrificus snake venom. These properties evaluation was performed in vitro using the methodologies: phospholipase assay, hemolytic assay, thrombolytic, coagulation assay, and proteolytic assay on fibrinogen, casein and BAPNA as substrates. The compounds were incubated previously with snake venoms, for 30 minutes at room temperature before each test. The compounds evaluated presented inhibitions for all activities, except for thrombotic activity of Crotalus durissus terrificus venom. The most pronounced inhibitions (30 - 65%) occurred against proteases, and in a lesser proportion phospholipases A2, inhibited on an average of 30%. Based on our results, the compounds here utilized possess a potential to control in vitro, the toxic effects induced by snake venoms, here utilized.